Incorporação de nanopartículas cristalinas de niobato de lantânio em vidro telurito para obtenção de vitrocerâmica funcional - Batista, Gislene (2018)
This research proposed a method to prepare glass-ceramics by the incorporation of nanocrystals of lanthanum niobate (LaNbO4) in a tellurite glass. These nanocrystals doped with Eu3+ were prepared by spray-pyrolysis method. The glass-ceramic was made by the incorporation of the nanocrystals in glasses with different molar compositions of the system TeO2-GeO2-Nb2O5-K2O-Li2O using two different methods of incorporating. For some of the glass-ceramics, before the incorporation, the nanocrystals suffered a thermal treatment. By the visual analysis, it was noticed that the nanocrystals gave opacity to the material depending on the percentage incorporated, and that with the time’s raising, or increase of incorporation temperature they became transparent. In addition, that with the thermal treatment in the nanocrystals was realized what it is possible the presence of the nanocrystals’ aggregate in the glass. By the thermal analysis were observed the increase in glass transition temperature values ​​with the time of permanence of the material in the furnace that could indicate the dispersion and the dissolution of nanocrystals; and this value did not change in the glass-ceramics with the nanocrystals’ aggregate. The high transparency window of these materials was observed by ultraviolet-visible absorption spectroscopy and infrared transmittance spectroscopy. No crystalline peaks were detected in X ray diffractogram for most of the samples probably because of the low percentage of nanocrystals, but the peaks of lanthanum niobate monoclinic phase were identified in the glass-ceramic within less time in the furnace. Raman spectroscopy did not show difference between the samples and the glasses. In the photoluminescence analysis, the peaks were widened in the analyzed samples, especially in that without thermal treatment in nanocrystals, probably because of the Eu3+ dispersion in the glass. Besides, difference in the more effective wavelength for luminescence was observed among the samples, possibly because of the difference in the cut off wavelengths absorption. By luminescence parameters, it was realized that the samples that remained less time in the furnace and with the nanocrystals’ aggregate had larger values ​​of quantum efficiency.